A proposed plan of supervision of health instruction in the public elementary schools in the city of Manila - Gregorio, Elisa (Jimena) 1921 ([Quezon City s.n.], 1973)
This study presents a proposed plan of supervision of health instruction in the public elementary schools of Manila. Specifically, this study seeks to know what pattern of health instruction is provided for in the public elementary schools in the City of Manila, what supervisory practices are utilized to enhance health instruction in these schools, and what plan of supervision may be suggested for a better health instruction program in the Division of City Schools, Manila. In the study, supervisory practices are re-examined through a survey of such practices as perceived by the teachers. The survey is expected to reveal the strength and weaknesses of the supervisory program to help supervisors establish or reorganize a plan for efficient supervision.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Health education (Elementary) -- School supervision, Elementary. -- Manila